Effects of organic amendments on the natural attenuation of radiocesium transferability in grassland soils with high potassium fertility. (June 2020) - Takeda, Akira; Tsukada, Hirofumi; Unno, Yusuke; Takaku, Yuichi; Hisamatsu, Shun'ichi
Abstract: Organic amendments affect the behavior of radiocesium in soil-plant systems in a complex way; they can inhibit radiocesium fixation by clay minerals by blocking selective sorption sites, whereas K supplied to the soil solution by amendments can reduce Cs uptake by plant roots. Here, we investigated the influence of inorganic and organic amendments on the transferability of radiocesium from soil to grass seedling in a humus-rich Andosol with high exchangeable K content. Soil samples were spiked with a 137 Cs tracer, treated with N, N–P–K, compost (cattle manure using rice straw), or no amendment (control soil), and subjected to repeated two-week wetting and air-drying treatments for one year in an artificial climate chamber. Small-scale cultivations of orchard grass were performed four times during the experimental period to assess temporal changes of availability of 137 Cs in the soils. The 137 Cs transfer factor (TF), defined as the 137 Cs concentration in the plant divided by that in the soil, decreased with time in the control soil. The soil treated with compost showed higher TFs than the control soil in each cultivation and a slower attenuation of 137 Cs transferability. By comparing the extractability of 137 Cs, NH4 +, and K + with the observed TFs, we show that K released from the compost was not effective in reducing root uptake of 137 Cs, but enhanced 137 Cs desorption from the soil under K-rich conditions. This result suggests that organic amendment is ineffective in reducing root uptake of radiocesium under high exchangeable K concentrations, and may instead enhance the long-term availability of radiocesium in soils. Highlights: Availability of 137 Cs spiked to a soil rich in exchangeable K was determined. Soil amended with compost maintained higher water-extractable K in soil. Higher 137 Cs transferability to grass was also observed in soil applied with compost. Organic amendment can increase Cs availability in soils under K-rich conditions.